Development of FPGA based power flow monitoring system in a microgrid - Ozdemir, Mahmut Temel; Sonmez, Mehmet; Akbal, Ayhan (Pergamon-Elsevier Science Ltd, 2014)
In recent decades, smart grid has become increasingly attractive to both energy producers and consumers. Amongst the main challenges for the successful realization of smart grid includes the integration of renewable energy resources, real time demand response and management of intermittent energy resources. Apart from smart grid, the development of micro-grids should take into consideration of issues such as the system performance, modelling, monitoring and controlling of the micro-grids. In particular, the recent advancements in information and communication technologies (ICTs) could facilitate the effective development of the future micro-grid system. The goal of the study is design of a system, based on FPGA, which monitors the power flow of the Microgrids. First of all a MG system installed in the laboratory of Firat University Electrical and Electronics Engineering Department consists of 1.2 kWp grid connected PV system, 5 kW micro hydro turbine, 0.5 kW wind turbine and 0.1 kW fuel cell unit was introduced. Afterwards, for smart-grids, a system of power flow that has a powerful high sampling rate was dwelt upon. During implementations, the data collected from the power system was transmitted to the FPGA cards located in open area by wireless data-monitoring card. This study has contributed to studies of other researchers by means of the monitoring system which has a high sampling frequency. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cell; PV; Wind energy; Micro hydro energy; FPGA based power flow monitoring